The Old English Poem "A Vampyre of the Fens": A Bibliographical Ghost - Olivares Merino, Eugenio (Miscelánea: A Journal of English and American Studies, 2005)
Dudley Wrights’ book Vampires and Vampirism (1914) might well be said to be the first serious attempt in English to compile vampire stories and reports from all over the world, as well as to elucidate how far a certain amount of scientific truth might underlie these accounts. In this work, the author makes a statement that has passed unnoticed for both Anglosaxonists and vampire hunters: ‘There is an Anglo-Saxon poem with the title A Vampyre of the Fens (186). The veracity of this claim is demolished by the fact that students and scholars of Old English literature well know that such a poem does not exist. Besides, the dearth of vampiric literature in England before William of Malmesbury, William of Newburgh or Walter Map is widely attested. Finally, it is significant that the term ‘vampyre’ was not used in English until 1734, as reported by the Oxford English Dictionary. The evidence that refutes Wrights affirmation is, as we can see, overwhelming, and yet there is some truth in his words.
Keywords: Vampyre; Theory of reception; Beowulf; Victorian England